The metallostibine Os2(CO)8(μ-SbPh) : a versatile donor precursor for antimony-containing heterometallic clusters - Li, Ying-Zhou (2019)
The metallostibine Os2(CO)8(μ-SbPh), 2, acts as a good two-electron donor ligand, reacting readily with Group 8 metal carbonyls to give heterometallic clusters. Specifically, it undergoes ligand substitution reaction with Fe2(CO)9, Os3(CO)11(CH3CN), or Os3(CO)10(CH3CN)2 to afford Os2Fe(CO)12(μ3-SbPh), 3, Os5(CO)19(μ3-SbPh), 4, or Os7(CO)26(μ3-SbPh)2, 5, respectively, in moderate to high yields. An analogous reaction with Ru3(CO)11(CH3CN) afforded another spirocyclic cluster Os3Ru(CO)14(μ-PhCO)(μ4-Sb), 9. UV irradiation of 4 afforded the spirocyclic clusters Os5(CO)18(μ,η2-PhCO)(μ4-Sb), 6, and Os5(CO)18(μ,η2-C6H4)(μ-H)(μ4-Sb), 7, while the raft-like cluster Os5(CO)19(μ3-SbPh), 8, was obtained when a methanolic solution was exposed to natural light; cluster 5 failed to react under similar conditions. All the new clusters have been characterized spectroscopically and crystallographically, and possible pathways for the formation of 6-9 proposed.